Audit Quality and Technology Factors in Auditing in the Digital Age: Faktor Kualitas Audit dan Teknologi dalam Audit di Era Digital - Akuba, Ichlasul Amal; Amiruddinn (Indonesian Journal of Innovation Studies, 2025)
General Background: Audit quality plays a critical role in ensuring the reliability of financial reporting and the integrity of corporate governance, especially in the digital era where data complexity is increasing. Specific Background: Previous studies have explored various factors influencing audit quality, including auditor competence, independence, workload, and firm characteristics. However, research integrating these with the impact of digital technology remains limited. Knowledge Gap: There is a lack of comprehensive understanding of how technological advancement, combined with internal and external audit factors, influences audit quality in the modern audit landscape. Aims: This study conducts a Systematic Literature Review (SLR) of Scopus-indexed articles (2014–2024) to identify key internal and external factors that affect audit quality and examine the role of technology in supporting high-quality audits. Results: The review finds that factors such as auditor competence, stress, workload balance, and audit team dynamics significantly affect audit quality. Technological tools like AI and data analytics enhance efficiency, risk detection, and audit documentation. Novelty: This study uniquely combines audit quality determinants with the role of digital technology, offering a multidimensional synthesis rarely addressed in prior literature. Implications: The findings offer practical insights for public accounting firms, regulators, and educators to enhance audit standards through technology integration, workload management, and auditor independence.Highlight : Audit quality is influenced by both internal (e.g., workload, team competence) and external (e.g., social ties, rotation timing) factors. Digital tools like AI and data analytics enhance audit effectiveness, reduce error, and support remote auditing. Systematic literature review reveals a gap in studies integrating digital readiness with audit quality improvement. Keywords : Audit Quality, Digital Technology, Auditor Competence, Systematic Review, Audit Independence